Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Yao, Linlin; Zhao, Bin; Wang, Qi; Jiang, Xuyang; Han, Sha; Hu, Wei; Li, Chenglin (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus. The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.